Bacteriostatic and bactericidal modes of action of bis(tributyltin)oxide on Legionella pneumophila. - Soracco, R J (1983)
The modes of action of bis(tributyltin)oxide (TBTO) doses between 1 X 10(4) and 6 X 10(7) molecules per cell on a single environmental isolate of Legionella pneumophila were studied by monitoring the following parameters: (i) growth, (ii) cell viability, (iii) 14C-amino acid incorporation, (iv) 14CO2 production from 14C-amino acids, (v) [3H]uridine incorporation, (vi) [3H]thymidine incorporation, (vii) oxygen consumption, (viii) cellular ATP levels, and (ix) adenylate energy charge. The amount of TBTO associated with the cells in these laboratory cultures was also compared with that remaining in the suspending medium. Most of the TBTO (68 to 88%) was found to be associated with the cells. This result explained why the cellular responses which were measured did not correlate with the TBTO concentration, but rather with the dose of TBTO to which the cells were exposed. At the lower TBTO doses tested (10(4) to 10(7) molecules per cell) a log-normal relationship was observed between the reduction in growth rate and the TBTO concentration. At intermediate TBTO doses (ca. 10(7) molecules per cell) growth stasis occurred, with nearly 100% of the cells in these cultures remaining viable for at least 5 h after treatment. The cellular function which seemed to be primarily affected at these levels of TBTO was the energy conversion mechanism, since the decline in the rates of CO2 production, oxygen consumption, and macromolecular synthesis was preceded by an immediate (within 1 min) drop in the intracellular levels of ATP and the adenylate energy charge. At the higher TBTO doses greater than 10(7) molecules per cell) an initial, precipitous, drop in the number of viable cells was observed, which was followed by a further exponential reduction of viable cells in the treated culture. This dramatic increase in bactericidal activity with a slight increase in the TBTO dose indicated that the modes of bacteriostatic and bactericidal action of TBTO were different.